DIGITALISASI LAPORAN KEUANGAN BUMDES SRIKANDI GEMILANG PADA APLIKASI BERBASIS MICROSOFT EXCEL - Sherilliya Roselitha; Bintang Wahyu Prayogo; Mohammad Reihan; Rendy Chairul Ramadhany; Nabilla Alya Ramanda Putri (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Financial reports are documents that contain the financial position and performance of a company in a certain period. In general, financial reports consist of a balance sheet, income statement, statement of changes in equity, cash flow statement and notes to the financial statements. In Tegalwangi Village there is a Bumdes savings and loans in the business unit, financial reports are very important because they provide to ensure transparency and accountability to stakeholders and support risk management. The purpose of this activity is to assist in the implementation of digitalization in writing financial reports through applications that have been provided in Tegalwangi Village. The method used in this activity is to see field conditions directly, then find out the problems that are happening and provide appropriate suggestions or solutions